Electrode assembly, battery cell, battery pack, and electric device

CN122822703APending Publication Date: 2026-09-25SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611139739.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

[0004]本申请旨在提供一种电极组件、电池单体、电池包及用电装置,以解决锂离子的传输效率较低的问题

Benefits of technology

[0037]在本申请的实施例中,有益效果为隔膜设置在正极片与负极片之间,隔膜的透气度限制为95s/100cc到150s/100cc之间。隔膜实现低透气度、高孔隙率,使得锂离子穿过隔膜的阻力较低,从而锂离子在电极组件内部的传输效率较高、电池的内阻较低,对应的电极组件能够较好地满足高倍率充放电需求;还可避免因透气度太高导致隔膜丧失对正负极片的隔离效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122822703A_ABST
    Figure CN122822703A_ABST
Patent Text Reader

Abstract

The application discloses an electrode assembly, a battery monomer, a battery pack and a power utilization device. A positive electrode current collector has a positive electrode coating part and a positive electrode uncoating part, a positive electrode active material is coated on the positive electrode coating part, and the positive electrode coating part and the positive electrode uncoating part are arranged along the width direction of a positive electrode sheet. A negative electrode current collector has a negative electrode coating part and a negative electrode uncoating part, a negative electrode active material is coated on the negative electrode coating part, and the negative electrode coating part and the negative electrode uncoating part are arranged along the width direction of a negative electrode sheet. A diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, the air permeability of the diaphragm is greater than or equal to 95 s / 100 cc and less than or equal to 150 s / 100 cc. The diaphragm of the application realizes a diaphragm with low air permeability and high porosity, so that the resistance of lithium ions passing through the diaphragm is low, the transmission efficiency of lithium ions in the electrode assembly is high, the internal resistance of the battery is low, and the corresponding electrode assembly can better meet the high-rate charging and discharging demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to an electrode assembly, a battery cell, a battery pack, and an electrical device. Background Technology

[0002] With the development of new energy sources, more and more fields are adopting new energy as their power source. Due to their advantages such as high energy density, rechargeability, safety, and environmental friendliness, battery cells are widely used in new energy vehicles, consumer electronics, and energy storage systems. The electrode assembly includes a positive electrode, a negative electrode, and a separator. The separator is positioned between the positive and negative electrodes to isolate them and prevent short circuits. During the operation of the electrode assembly, lithium ions can pass through the separator to flow between the positive and negative electrodes.

[0003] Among related technologies, lithium-ion transport efficiency is relatively low. Summary of the Invention

[0004] This application aims to provide an electrode assembly, a battery cell, a battery pack, and an electrical device to solve the problem of low lithium-ion transport efficiency.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows: In a first aspect, embodiments of this application provide an electrode assembly, comprising: A positive electrode sheet includes a positive current collector and a positive active material. The positive current collector has a positive electrode coated portion and a positive electrode uncoated portion. The positive active material is coated on the positive electrode coated portion. The positive electrode coated portion and the positive electrode uncoated portion are arranged along the width direction of the positive electrode sheet. A negative electrode sheet includes a negative electrode current collector and a negative electrode active material. The negative electrode current collector has a negative electrode coated portion and a negative electrode uncoated portion. The negative electrode active material is coated on the negative electrode coated portion. The negative electrode coated portion and the negative electrode uncoated portion are arranged along the width direction of the negative electrode sheet. A separator is disposed between the positive electrode and the negative electrode, and the air permeability of the separator is greater than or equal to 95s / 100cc and less than or equal to 150s / 100cc.

[0006] According to some embodiments of this application, the diaphragm includes at least one polyolefin layer.

[0007] According to some embodiments of this application, the diaphragm comprises only a polyolefin layer.

[0008] According to some embodiments of this application, along the thickness direction of the separator, at least one polyolefin layer is located on the outermost side of the separator, and the polyolefin layer is in direct contact with the positive electrode plate, and / or, at least one polyolefin layer is located on the outermost side of the separator, and the polyolefin layer is in direct contact with the negative electrode plate.

[0009] According to some embodiments of this application, the polyolefin layer includes a first fiber and a second fiber. The first fiber extends along the length direction of the diaphragm, and the second fiber extends along the width direction of the diaphragm. There are multiple first fibers, and a second fiber is disposed between two adjacent first fibers along the width direction of the diaphragm.

[0010] According to some embodiments of this application, the diameter of the first fiber is larger than the diameter of the second fiber.

[0011] According to some embodiments of this application, the diameter of the first fiber is greater than or equal to 80 nm and less than or equal to 400 nm, and / or the diameter of the second fiber is greater than or equal to 5 nm and less than or equal to 79 nm.

[0012] According to some embodiments of this application, along the width direction of the diaphragm, the size of the second fiber is greater than or equal to 50 nm and less than or equal to 500 nm.

[0013] According to some embodiments of this application, the polyolefin layer is configured to have a plurality of preset regions with an area of ​​1μm*1μm, wherein the difference in diameter between any two first fibers within any preset region is less than or equal to 300nm.

[0014] According to some embodiments of this application, the polyolefin layer is configured to have a plurality of preset regions with an area of ​​1μm*1μm, wherein the difference in diameter between any two points of any first fiber within any preset region is less than or equal to 300nm.

[0015] According to some embodiments of this application, the number of the second fibers is multiple, and the multiple second fibers are arranged at intervals along the length direction of the diaphragm.

[0016] According to some embodiments of this application, along the length direction of the diaphragm, the distance between two adjacent second fibers is greater than or equal to the diameter of the second fiber.

[0017] According to some embodiments of this application, the polyolefin layer further includes a third fiber extending along the width direction of the diaphragm. Along the width direction of the diaphragm, the third fiber is disposed between two adjacent first fibers. The diameter of the third fiber is greater than the diameter of the second fiber. The diameter of the third fiber is greater than or equal to 80 nm and less than or equal to 400 nm.

[0018] According to some embodiments of this application, the number of polyolefin layers is multiple, and the multiple polyolefin layers are stacked along the thickness direction of the membrane. At least one polyolefin layer is a first polyolefin layer, and at least one polyolefin layer is a second polyolefin layer. The first polyolefin layer and the second polyolefin layer are made of different materials.

[0019] According to some embodiments of this application, the diaphragm includes a first polyolefin layer and a second polyolefin layer stacked together.

[0020] According to some embodiments of this application, the diaphragm includes a first polyolefin layer, a second polyolefin layer, and the first polyolefin layer stacked together.

[0021] According to some embodiments of this application, the number of polyolefin layers is multiple, and the multiple polyolefin layers are stacked along the thickness direction of the membrane. At least one polyolefin layer is a first polyolefin layer, and at least one polyolefin layer is a second polyolefin layer. The first polyolefin layer and the second polyolefin layer have different air permeability.

[0022] According to some embodiments of this application, the number of the first polyolefin layer is two, the number of the second polyolefin layer is one, and the second polyolefin layer is located between the two first polyolefin layers along the thickness direction of the membrane. The air permeability of the first polyolefin layer is less than that of the second polyolefin layer.

[0023] According to some embodiments of this application, the electrode assembly is of the wound type.

[0024] According to some embodiments of this application, the uncoated positive electrode portion extends along the length direction of the positive electrode sheet, and the size of the uncoated positive electrode portion is equal to the size of the coated positive electrode portion; and / or, the uncoated negative electrode portion extends along the length direction of the negative electrode sheet, and the size of the uncoated negative electrode portion is equal to the size of the coated negative electrode portion.

[0025] According to some embodiments of this application, along the width direction of the positive electrode sheet, the ratio of the size of the uncoated portion of the positive electrode to the size of the positive electrode sheet is greater than or equal to 3% and less than or equal to 8%, and / or, along the width direction of the negative electrode sheet, the ratio of the size of the uncoated portion of the negative electrode to the size of the negative electrode sheet is greater than or equal to 3% and less than or equal to 8%.

[0026] According to some embodiments of this application, along the length direction of the electrode assembly, the uncoated positive electrode portion and the uncoated negative electrode portion are respectively located at opposite ends of the electrode assembly.

[0027] According to some embodiments of this application, the thickness of the diaphragm is greater than or equal to 6 μm and less than or equal to 20 μm.

[0028] According to some embodiments of this application, the electrode assembly includes at least one of the following: Along the length of the electrode assembly, the size of the electrode assembly is greater than or equal to 120 mm and less than or equal to 150 mm; Along the width direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 60 mm and less than or equal to 80 mm; Along the thickness direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 12 mm and less than or equal to 20 mm.

[0029] According to some embodiments of this application, the diaphragm is made of at least one of polyethylene and polypropylene.

[0030] According to some embodiments of this application, the positive electrode active material includes at least one of secondary spherical particles, single crystal particles, and single crystal-like particles.

[0031] According to some embodiments of this application, the positive electrode active material includes secondary spherical particles, and the positive electrode active material has a porous structure.

[0032] According to some embodiments of this application, the positive electrode active material includes a layered lithium transition metal oxide; the transition metal in the layered lithium transition metal oxide includes nickel and manganese; and the molar percentage of nickel in the transition metal is 30% to 55%, and the molar percentage of manganese in the transition metal is 25% to 35%.

[0033] According to some embodiments of this application, the positive electrode active material includes lithium iron phosphate.

[0034] Secondly, embodiments of this application propose a battery cell including the electrode assembly of any one of the above.

[0035] Thirdly, embodiments of this application propose a battery pack comprising any of the aforementioned battery cells.

[0036] Fourthly, embodiments of this application provide an electrical device including a battery pack comprising any of the above-mentioned components.

[0037] In the embodiments of this application, the beneficial effect is that the separator is disposed between the positive and negative electrode plates, and the permeability of the separator is limited to between 95s / 100cc and 150s / 100cc. The separator achieves low permeability and high porosity, resulting in lower resistance for lithium ions to pass through the separator. This leads to higher lithium ion transport efficiency within the electrode assembly and lower internal resistance of the battery, allowing the electrode assembly to better meet the requirements of high-rate charging and discharging. Furthermore, it avoids the separator losing its isolation effect on the positive and negative electrode plates due to excessively high permeability.

[0038] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0039] The present application will be further described below with reference to the accompanying drawings and embodiments, wherein: Figure 1 Exploded views of the electrode assembly structure in some embodiments of this application; Figure 2 Here are simplified structural diagrams of the positive electrode sheet in some embodiments of this application; Figure 3 Here are simplified structural diagrams of the negative electrode sheet in some embodiments of this application; Figure 4 This is a simplified structural diagram of the diaphragm in some embodiments of this application; Figure 5 These are scanning electron microscope (SEM) images of the polyolefin layer in some embodiments of this application; Figure 6 This is a simplified structural diagram of the electrode assembly in some embodiments of this application.

[0040] Figure label: 100, Positive electrode sheet; 110, Positive current collector; 110a, Positive electrode coated portion; 110b, Positive electrode uncoated portion; 120, Positive electrode active material; 200, Negative electrode sheet; 210, Negative electrode current collector; 210a, Negative electrode coated portion; 210b, Negative electrode uncoated portion; 220, Negative electrode active material; 300, Separator; 310, Polyolefin layer; 310a, First polyolefin layer; 310b, Second polyolefin layer; 311, First fiber; 312, Second fiber; 313, Third fiber. Detailed Implementation

[0041] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0042] In the description of this application, it should be understood that the orientation descriptions, such as up, down, front, back, left, right, etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0043] In the description of this application, "several" means one or more, "multiple" means two or more, "greater than," "less than," and "exceeding" are understood to exclude the stated number, while "above," "below," and "within" are understood to include the stated number. The use of "first" and "second" in the description is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, or implicitly indicating the number of indicated technical features, or implicitly indicating the order of the indicated technical features.

[0044] In the description of this application, unless otherwise expressly defined, terms such as "setup," "installation," and "connection" should be interpreted broadly, and those skilled in the art can reasonably determine the specific meaning of the above terms in this application in conjunction with the specific content of the technical solution.

[0045] In the description of this application, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0046] Currently, judging from market trends, the application of battery cells is becoming increasingly widespread. Battery cells are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but also extensively in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in aerospace and other fields. With the continuous expansion of the application areas of battery cells, the market demand is also constantly increasing.

[0047] In related technologies, the electrode assembly includes a positive electrode, a negative electrode, and a separator. The separator is positioned between the positive and negative electrodes to isolate them and prevent short circuits. During the charging and discharging process of the electrode assembly, lithium ions can pass through the separator and flow between the positive and negative electrodes. The surface of the separator is typically coated with an adhesive layer to bond it to the positive and negative electrodes. This adhesive layer can affect the permeability of the separator to some extent, leading to lower lithium-ion transport efficiency.

[0048] The air permeability of the separator 300 in this embodiment is limited to 95s / 100cc to 150s / 100cc. The low air permeability of the separator 300 can improve the lithium-ion transport efficiency, resulting in a faster charge and discharge speed for the corresponding battery cell.

[0049] This application provides an electrical device, which includes a battery pack and a device body.

[0050] Electrical devices can be, for example, mobile phones, portable devices, laptops, electric vehicles, electric toys, power tools, vehicles, ships, and spacecraft.

[0051] The technical solutions described in this application are not limited to the devices described above, but can also be applied to all devices that use battery packs.

[0052] The battery pack mentioned in the embodiments of this application may include one or more battery modules for providing voltage and capacity. A battery module may include multiple battery cells, which are connected in series, parallel, or mixed connections via a busbar.

[0053] In some embodiments of this application, the battery cell can be a secondary battery, which refers to a battery cell that can be recharged to activate the active materials and continue to be used after the battery cell has been discharged.

[0054] The battery cell can be a lithium-ion battery, sodium-ion battery, sodium-lithium-ion battery, lithium metal battery, sodium metal battery, lithium-sulfur battery, magnesium-ion battery, nickel-metal hydride battery, nickel-cadmium battery, lead-acid battery, etc., and the embodiments of this application are not limited to this.

[0055] This application also provides an electrode assembly; please refer to [link / reference]. Figures 1 to 3 and Figure 6The electrode assembly includes a positive electrode 100, a negative electrode 200, and a separator 300. The positive electrode 100 includes a positive current collector 110 and a positive active material 120. The positive current collector 110 has a positive electrode coated portion 110a and a positive electrode uncoated portion 110b. The positive active material 120 is coated on the positive electrode coated portion 110a. The positive electrode coated portion 110a and the positive electrode uncoated portion 110b are arranged along the length of the electrode assembly. The positive active material 120 is not disposed on the positive electrode uncoated portion 110b. The negative electrode 200 includes a negative electrode current collector 210 and a negative electrode active material 220. The negative electrode current collector 210 has a negative electrode coated portion 210a and a negative electrode uncoated portion 210b. The negative electrode active material 220 is coated on the negative electrode coated portion 210a. The negative electrode coated portion 210a and the negative electrode uncoated portion 210b are arranged along the length of the electrode assembly. The negative electrode uncoated portion 210b is not provided with the negative electrode active material 220. It is understood that the width direction of the positive electrode 100 and the negative electrode 200 refers to the width direction of the positive electrode 100 and the negative electrode 200 in their unfolded state. For example, when the electrode assembly is a wound cell, the width direction of the positive electrode 100 and the negative electrode 200 is parallel to the length direction of the electrode assembly, as shown in the figure. Figure 1 The direction indicated by the middle arrow R1. A separator 300 is disposed between the positive electrode 100 and the negative electrode 200. The air permeability of the separator 300 is greater than or equal to 95 s / 100cc and less than or equal to 150 s / 100cc. For example, the air permeability of the separator 300 can be a range of one or both of the following: 95 s / 100cc, 100 s / 100cc, 105 s / 100cc, 115 s / 100cc, 125 s / 100cc, 135 s / 100cc, 140 s / 100cc, 145 s / 100cc, or 150 s / 100cc. Understandably, the air permeability of the 300 membrane can be obtained through an air permeability test. Specifically, the air permeability test can be conducted, for example, according to standard GB / T36363-2018 "Test of Air Permeability of Polyolefin Separators for Lithium-ion Batteries," under normal pressure, with the testing instrument applying a pressure of 1.21 kPa, measuring the area through which 100 ml of air can pass as 6.45 cm². 2 The required time for membrane testing can be determined using a Gurly 4110N air permeability meter.

[0056] In the embodiments of this application, the beneficial effect is that the separator 300 is disposed between the positive electrode 100 and the negative electrode 200, and the permeability of the separator 300 is limited to between 95s / 100cc and 150s / 100cc. The separator 300 achieves low permeability and high porosity, resulting in lower resistance for lithium ions to pass through the separator 300, higher lithium ion transport efficiency within the electrode assembly, and lower internal resistance of the battery. The corresponding electrode assembly can better meet the requirements of high-rate charging and discharging; it also avoids the separator losing its isolation effect on the positive and negative electrodes due to excessive permeability.

[0057] In some embodiments, please refer to Figure 4 The separator 300 includes at least one polyolefin layer 310. Polyolefin material has good mechanical strength and toughness, and the separator 300 is relatively easy to process. Furthermore, polyolefin material has a defined pore-closing temperature. When the electrode assembly abnormally heats up due to overcharging or short circuit, the separator 300 will melt and shrink upon reaching its melting point, causing the micropores to close. This prevents lithium ions from passing through the separator 300, cutting off current generation from inside the electrode assembly and reducing the probability of thermal runaway.

[0058] In some embodiments, please refer to Figure 4 The separator 300 comprises only a polyolefin layer 310, and / or, along the thickness direction of the separator 300, at least one polyolefin layer 310 is located on the outermost side of the separator 300, directly contacting the positive electrode 100, and at least one polyolefin layer 310 is located on the outermost side of the separator 300, directly contacting the negative electrode 200. No other coating is provided on the surface of the polyolefin layer 310 of the separator 300, thus allowing the surface of the polyolefin layer 310 to directly contact the active materials of the positive electrode 100 and the negative electrode 200. No adhesive layer is provided on the surface of the separator 300, thus enabling the separator 300 to achieve low air permeability and high porosity, allowing lithium ions to pass through the polyolefin layer 310 relatively smoothly, resulting in low internal resistance of the electrode assembly. It is understood that the separator 300 can be bonded to the positive electrode 100 and the negative electrode 200 by applying external pressure.

[0059] In some embodiments, please refer to Figure 5The polyolefin layer 310 includes interconnected first fibers 311 and second fibers 312. The first fibers 311 extend along the length direction of the separator 300, and the second fibers 312 extend along the width direction of the separator 300. There are multiple first fibers 311. A second fiber 312 is disposed between two adjacent first fibers 311 along the width direction of the separator 300, forming a mesh structure. It is understood that the first fibers 311 and second fibers 312 can be formed by applying a tensile force parallel to the width direction of the separator 300 to the polyolefin layer 310. The mesh structure of the polyolefin layer 310 can increase the blocking area of ​​the separator 300 to a certain extent, and can also conveniently reduce the air permeability of the separator 300. The separator 300 can stably isolate the positive electrode 100 and the negative electrode 200.

[0060] In some embodiments, please refer to Figure 5 The diameter of the first fiber 311 is larger than the diameter of the second fiber 312. It can be understood that the first fiber 311 extends along the length of the diaphragm 300, and the second fiber 312 is connected to the first fiber 311 and located between two adjacent first fibers 311. The length of the first fiber 311 is significantly greater than the length of the second fiber 312. Since the diameter of the first fiber 311 is greater than the diameter of the second fiber 312, the strength of the first fiber 311 is greater than the strength of the second fiber 312. During the winding or operation of the diaphragm 300, the diaphragm 300 can maintain better stability, reducing the possibility of tape breakage.

[0061] In some embodiments, please refer to Figure 5The diameter of the first fiber 311 is greater than or equal to 80 nm and less than or equal to 400 nm. Exemplarily, the diameter of the first fiber 311 can be any one or both of the following: 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 370 nm, 380 nm, 390 nm, or 400 nm. The diameter of the second fiber 312 is greater than or equal to 5 nm and less than or equal to 79 nm. Exemplarily, the diameter of the second fiber 312 can be any one or both of the following: 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 75 nm, or 79 nm. The appropriate range of diameters for the first fiber 311 and the second fiber 312 allows the corresponding diaphragm 300 to have low air permeability while also ensuring good strength and reducing the likelihood of diaphragm breakage. It is understood that the first fiber 311 and the second fiber 312 can be observed under an electron microscope, and the diameters of the first fiber 311 and the second fiber 312 can be measured under the viewpoint of the electron microscope. The diameters of the first fiber 311 and the second fiber 312 measured at any position all meet the above-mentioned range of values.

[0062] In some embodiments, the polyolefin layer 310 has multiple preset regions, and within any preset region, the difference in diameter between any two first fibers 311 is less than or equal to 300 nm. It is understood that the embodiments of this application do not limit the number, shape, or size of the preset regions. For example, the shape of the preset region can be circular, square, or rectangular. Specifically, to facilitate the measurement of the diameter difference between any two first fibers 311 within the preset region, the shape of the preset region can be set to a 1 μm * 1 μm square. After determining the preset region using an electron microscope, the diameter difference between any two first fibers 311 within the preset region is less than or equal to 300 nm. It is understood that along the extension direction of the first fiber, the diameter of a single first fiber may fluctuate to some extent. For example, within any preset region, the diameter difference between any two points on any first fiber 311 is less than or equal to 300 nm. The small difference in diameter between any two first fibers 311 and the small difference between any two points of any first fiber 311 can reflect that the diameter of the first fiber 311 in the polyolefin layer 310 is relatively uniform, the lithium ion transport is relatively uniform, and thus the lithium ion is deposited more uniformly on the electrode, reducing the occurrence of lithium plating in the electrode assembly.

[0063] In some embodiments, please refer to Figure 5The number of second fibers 312 is multiple, and the multiple second fibers 312 are arranged at intervals along the length direction of the separator 300 to form pores. The multiple second fibers 312 are arranged at intervals, and the pores formed between the second fibers have a large porosity, so that lithium ions can flow more smoothly from the pores between two adjacent second fibers 312, thereby further reducing the air permeability of the separator 300.

[0064] In some embodiments, please refer to Figure 5 Along the length of the separator 300, the distance between two adjacent second fibers 312 is greater than or equal to the diameter of the second fiber 312. A larger distance between two adjacent second fibers 312 allows the corresponding separator 300 to have a larger pore size structure, which can significantly reduce the air permeability of the separator 300, thereby further promoting lithium-ion transport and improving lithium-ion transport efficiency.

[0065] It is understood that other embodiments of this application are not limited to situations where the distance between two adjacent second fibers 312 is greater than or equal to the diameter of the second fiber 312 along the length direction of the diaphragm 300. Exemplarily, the distance between two adjacent second fibers 312 is less than the diameter of the second fiber 312 along the length direction of the diaphragm 300.

[0066] In some embodiments, please refer to Figure 5 The polyolefin layer 310 further includes a third fiber 313, which extends along the width direction of the diaphragm 300. Along the width direction of the diaphragm 300, the third fiber 313 is disposed between two adjacent first fibers 311. The diameter of the third fiber 313 is larger than the diameter of the second fiber 312, and the diameter of the third fiber 313 is greater than or equal to 80 nm and less than or equal to 400 nm. For example, the diameter of the third fiber 313 is larger than the diameter of the second fiber 312, and the extension direction of the third fiber 313 is parallel to the extension direction of the second fiber 312. The third fiber 313 can increase the strength of the diaphragm 300 along its width direction to a certain extent, thereby improving the puncture resistance of the diaphragm 300 and further enhancing the strength of the diaphragm 300.

[0067] In some embodiments, please refer to Figure 4 The diaphragm 300 has multiple polyolefin layers 310, which are stacked along the thickness direction of the diaphragm 300. At least one polyolefin layer 310 is a first polyolefin layer 310a, and at least one polyolefin layer 310 is a second polyolefin layer 310b. The first polyolefin layer 310a and the second polyolefin layer 310b are made of different materials. Using different materials for the multiple polyolefin layers 310 in the diaphragm 300 combines the advantages of both materials, resulting in better mechanical properties of the diaphragm 300.

[0068] It is understood that other embodiments of this application are not limited to the first polyolefin layer 310 and the second polyolefin layer 310 being made of different materials. For example, the first polyolefin layer 310 and the second polyolefin layer 310 are made of the same material, and both are made of polypropylene (PP) or polyethylene (PE).

[0069] In some embodiments, please refer to Figure 4 The separator 300 includes a first polyolefin layer 310a and a second polyolefin layer 310b stacked together, and the separator 300 is configured as a double-layer structure. In other embodiments, the separator 300 includes a first polyolefin layer 310a, a second polyolefin layer 310b, and a first polyolefin layer 310a stacked together. The separator 300 is configured as a "sandwich" structure. Exemplarily, along the thickness direction of the electrode assembly, the first polyolefin layers 310a on both sides are in contact with the positive electrode 100 and the negative electrode 200, respectively, and the interaction force and friction force generated by the first polyolefin layers 310a in contact with the positive electrode 100 and the negative electrode 200 are substantially the same. The separator 300 includes three polyolefin layers 310, and the separator 300 has a "sandwich" structure, which allows the separator 300 to have the advantages of multiple materials while also balancing the forces on the separator 300.

[0070] In some embodiments, the separator 300 is made of at least one of polyethylene and polypropylene. The polyolefin layer 310 of PE material has a low melting point. Under abnormal temperature conditions, the polyolefin layer 310 of PE material will melt first and close the micropores, thereby blocking the lithium-ion transport channels and reducing the probability of thermal runaway. On the other hand, the polyolefin layer 310 of PP material has a high melting point. Even when the polyolefin layer 310 of PE material melts, the polyolefin layer 310 of PP material can still provide mechanical support as the structural skeleton of the separator 300, preventing the positive electrode 100 and the negative electrode 200 from directly contacting and short-circuiting.

[0071] In some embodiments, the permeability of the first polyolefin layer 310a and the second polyolefin layer 310b is different. For example, there are two first polyolefin layers 310a and one second polyolefin layer 310b. Along the thickness direction of the separator 300, the second polyolefin layer 310b is located between the two first polyolefin layers 310a, and the permeability of the first polyolefin layers 310a is less than that of the second polyolefin layer 310b. When the separator 300 has a multilayer polyolefin layer 310 structure, a gradient permeability distribution is formed along the thickness direction of the separator 300. This can reduce the risk of pore collapse of the polyolefin layer 310 structure during the expansion and contraction of the positive electrode 100 and the negative electrode 200 while ensuring the mechanical strength of the separator 300, thereby further improving the cycle stability of the battery cell. It is understandable that the air permeability of different polyolefin layers 310 can be determined by testing the air permeability of different polyolefin layers 310 during the preparation process, measuring the cross-sectional morphology by CP+SEM, testing the porosity and thickness of different polyolefin layers 301, and obtaining the air permeability ratio of the finished membrane 300 according to the resistance ratio.

[0072] In some embodiments, please refer to Figure 1 The electrode assembly is a wound cell. During the processing of the electrode assembly, the positive electrode 100, the separator 300 and the negative electrode 200 are stacked along the thickness direction in advance, and then wound with a roller to form a wound cell similar to a "jelly roll".

[0073] In some embodiments, please refer to Figures 1 to 3 The uncoated positive electrode portion 110b extends along the length of the positive electrode sheet 100, and its size is equal to that of the coated positive electrode portion 110a. Similarly, the uncoated negative electrode portion 210b extends along the length of the negative electrode sheet 200, and its size is equal to that of the coated negative electrode portion 210a. The electrode assembly is a "full-tab cell," which further reduces the battery internal resistance of the electrode assembly, allowing it to better adapt to fast charging and high-rate discharge scenarios. For example, the length direction of the positive electrode sheet 100 is as follows... Figure 2 The direction indicated by the middle arrow R2 is the width direction of the positive electrode 100 as follows: Figure 2 The direction indicated by the middle arrow R3 is the length direction of the negative electrode 200 as follows: Figure 3 The direction indicated by the middle arrow R4 is the width direction of the negative electrode 200 as follows: Figure 3 The direction indicated by the middle arrow R5.

[0074] In some embodiments, along the width direction of the positive electrode 100, the ratio of the size of the uncoated portion 110b to the size of the positive electrode 100 is greater than or equal to 3% and less than or equal to 8%. Exemplarily, the ratio of the size of the uncoated portion 110b to the size of the positive electrode 100 can be a range of 3%, 4%, 5%, 6%, 7%, or 8%, or any two of these values. Along the width direction of the negative electrode 200, the ratio of the size of the uncoated portion 210b to the size of the negative electrode 200 is greater than or equal to 3% and less than or equal to 8%. Exemplarily, the ratio of the size of the uncoated portion 210b to the size of the negative electrode 200 can be a range of 3%, 4%, 5%, 6%, 7%, or 8%, or any two of these values. A suitable ratio of the uncoated portion to the corresponding electrode size allows the tab to have good strength and current carrying capacity, while also ensuring a high energy density for the electrode assembly. It is understandable that the dimensions of the uncoated positive electrode portion 110b, the positive electrode sheet 100, the uncoated negative electrode portion 210b, and the negative electrode sheet 200 can be obtained by measuring the electrode assembly under normal temperature and pressure using vernier calipers.

[0075] In some embodiments, please refer to Figure 1 Along the length of the electrode assembly, the uncoated positive electrode portion 110b and the uncoated negative electrode portion 210b are located at opposite ends of the electrode assembly. The uncoated positive electrode portion 110b and the uncoated negative electrode portion 210b, as positive and negative electrode tabs respectively, are located at opposite ends of the electrode assembly, facilitating connection with terminals or adapter plates during the processing of individual battery cells.

[0076] In some embodiments, the thickness of the diaphragm 300 is greater than or equal to 6 μm and less than or equal to 20 μm. Exemplarily, the thickness of the diaphragm 300 can be 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, or 20 μm. Maintaining a suitable thickness range for the diaphragm 300 ensures sufficient strength while minimizing its impact on the energy density of the electrode assembly.

[0077] In some embodiments, along the length direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 120 mm and less than or equal to 150 mm. Exemplarily, along the length direction of the electrode assembly, the size of the electrode assembly can be a range of 120 mm, 130 mm, 140 mm, or 150 mm, or any two of these values. Along the width direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 60 mm and less than or equal to 80 mm. Exemplarily, along the width direction of the electrode assembly, the size of the electrode assembly can be a range of 60 mm, 65 mm, 70 mm, 75 mm, or 80 mm, or any two of these values. Along the thickness direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 12 mm and less than or equal to 20 mm. Exemplarily, along the thickness direction of the electrode assembly, the size of the electrode assembly can be a range of 12 mm, 14 mm, 16 mm, 18 mm, or 20 mm, or any two of these values. The electrode assembly has a small overall size, which allows it to fit well with the diaphragm 300 without an adhesive layer. The diaphragm 300 can be stably bonded to the positive electrode 100 and the negative electrode 200. Understandably, the length, width, and thickness of the electrode assembly can be measured using vernier calipers under normal temperature and pressure conditions.

[0078] In some embodiments, the positive electrode active material includes at least one of secondary spherical particles, single-crystal particles, and single-crystal-like particles. Among them, secondary spherical particles are micron-sized spheres formed by the aggregation of nanoscale primary particles, exhibiting better kinetic performance and the ability to shorten the Li... + The diffusion path enhances rate performance, while the spherical particles offer excellent flowability, facilitating coating and rolling. Controllable compaction density allows for the design of internal voids to balance compaction density and ion transport. Combining these three elements comprehensively improves battery performance, achieving both high energy density and long lifespan, as well as a balance between kinetic performance and processability.

[0079] In some embodiments, the positive electrode active material comprises a layered lithium transition metal oxide; the transition metal in the layered lithium transition metal oxide comprises nickel and manganese; and the molar percentage of nickel in the transition metal is 30% to 55%, and the molar percentage of manganese in the transition metal is 25% to 35%. Exemplarily, the molar percentage of nickel in the transition metal can be any one or both of 30%, 35%, 40%, 45%, 50%, or 55%, and the molar percentage of manganese in the transition metal can be any one or both of 25%, 27%, 29%, 31%, 33%, or 35%. A nickel content of 30% to 55% ensures that the material has a sufficiently high reversible capacity, thereby enabling high-endurance, high-energy-density battery cells. A manganese content of 25% to 35% effectively stabilizes the layered structure, suppresses phase transitions and oxygen evolution at high potentials, thereby reducing the risk of thermal runaway. Through the synergistic effect of "high nickel providing capacity and high manganese stabilizing structure," capacity decay caused by particle cracking and interfacial side reactions during cycling can be effectively mitigated, thereby improving the cycle stability of the battery. Understandably, the nickel-cobalt content can be obtained through ICP-OES (inductively coupled plasma optical emission spectrometry).

[0080] In some embodiments, the positive electrode active material includes lithium iron phosphate. The electrode assembly exhibits high safety performance and a low risk of thermal runaway. Lithium iron phosphate has a unique olivine structure in which the PO covalent bonds are very strong, making it difficult to decompose and release large amounts of oxygen even under extreme conditions such as high temperature, overcharge, and over-discharge. This allows the corresponding electrode assembly to remain stable under conditions such as short circuits, compression, and needle penetration.

[0081] In some embodiments, the positive and negative electrode sheets are formed through processes such as slurry preparation, coating, drying, rolling, and slitting. The positive electrode sheet, separator, and negative electrode sheet are then stacked sequentially in the order of "positive electrode sheet-separator-negative electrode sheet-separator," and wound into a cylindrical or flat wound cell using a winding machine to form an electrode assembly. The electrode assembly is placed into the casing of the battery cell, and electrolyte is injected to ensure that the electrolyte fully wets the positive electrode sheet, negative electrode sheet, and separator. After electrolyte injection, the battery casing is sealed, and a formation process is performed to form a relatively stable SEI film on the surface of the negative electrode sheet, activating the battery cell's capacity. Finally, the battery cell after the formation process is subjected to charge-discharge tests, and its performance and safety are evaluated.

[0082] Example 1 This embodiment provides an electrode assembly, which includes the following components: The positive electrode sheet includes a positive current collector and a positive active material. The positive current collector has a coated portion and an uncoated portion. The positive active material is coated on the coated portion. The coated portion and the uncoated portion are arranged along the width direction of the positive electrode sheet, and the ratio of the size of the uncoated portion to the width of the positive electrode sheet is 5%. The positive active material is NCM523 (LiNi). 0.5 Co 0.2 Mn 0.3 O2), for example, the positive electrode active material is purchased from Minmetals New Energy Materials Co., Ltd.; the material coated on the positive electrode coating part is a mixture of positive electrode active material, positive electrode conductive agent SP and positive electrode binder PVDF in a mass ratio of 96:2:2. The positive electrode active material includes at least one of secondary spherical particles, single crystal particles and quasi-single crystal particles.

[0083] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material. The negative electrode current collector has a negative electrode coated portion and a negative electrode uncoated portion. The negative electrode active material is coated on the negative electrode coated portion. The negative electrode coated portion and the negative electrode uncoated portion are arranged along the width direction of the negative electrode sheet, and the ratio of the size of the negative electrode uncoated portion to the width of the negative electrode sheet is 5%. The negative electrode active material is artificial graphite. For example, the negative electrode active material is purchased from Shanghai Shanshan New Materials Co., Ltd. The material coated on the negative electrode coated portion is a mixture formed by the negative electrode active material, negative electrode conductive agent SP, negative electrode binder SBR and thickener CMC in a mass ratio of 96:1.5:1.5:1.

[0084] A separator, disposed between the positive and negative electrode plates, has an air permeability of 110s / 100cc. The separator comprises a polyolefin layer, which includes a first fiber and a second fiber. The first fiber extends along the length of the separator, and the second fiber extends along the width of the separator. Multiple first and second fibers are present. Multiple polyolefin layers are stacked along the thickness direction of the separator. The diameter of the first fiber is greater than or equal to 80nm and less than or equal to 400nm, and the diameter of the second fiber is greater than or equal to 5nm and less than or equal to 79nm. The separator is made of at least one of polyethylene and polypropylene. It is understood that the separator can be prepared via a dry process, with specific steps such as: batching—melting—three-layer co-extrusion casting—heat annealing / crystallization heat treatment—MD stretching—heat setting—winding—finished membrane.

[0085] Electrolyte, which wets the positive electrode, negative electrode and separator. For example, the electrolyte is purchased from Shenzhen Xinzhoubang Technology Co., Ltd., with a filling coefficient of 7 g / Ah.

[0086] All the above components are wrapped in aluminum-plastic film.

[0087] Example 2 This example provides an electrode assembly, which differs from Embodiment 1 in that: The air permeability of the diaphragm used is 130s / 100cc.

[0088] Example 3 This example provides an electrode assembly, which differs from Embodiment 1 in that: The air permeability of the diaphragm used is 150s / 100cc.

[0089] Example 4 This example provides an electrode assembly, which differs from Embodiment 1 in that: The air permeability of the diaphragm used is 95s / 100cc.

[0090] Example 5 This example provides an electrode assembly, which differs from Embodiment 1 in that: The ratio of the size of the uncoated portion of the positive electrode to the width of the positive electrode sheet is 3%, and the ratio of the size of the uncoated portion of the negative electrode to the width of the negative electrode sheet is 3%.

[0091] Example 6 This example provides an electrode assembly, which differs from Embodiment 1 in that: The ratio of the size of the uncoated portion of the positive electrode to the width of the positive electrode sheet is 8%, and the ratio of the size of the uncoated portion of the negative electrode to the width of the negative electrode sheet is 8%.

[0092] Comparative Example 1 This example provides an electrode assembly, which differs from Embodiment 1 in that: The air permeability of the diaphragm used is 70s / 100cc.

[0093] Comparative Example 2 This example provides an electrode assembly, which differs from Embodiment 1 in that: The air permeability of the diaphragm used is 170s / 100cc.

[0094] Comparative Example 3 This example provides an electrode assembly, which differs from Embodiment 1 in that: The diaphragm used has a coating on its surface, and its air permeability is 190s / 100cc.

[0095] Comparative Example 4 This example provides an electrode assembly, which differs from Embodiment 1 in that: The uncoated portion and the coated portion of the positive electrode are arranged along the length of the positive electrode sheet, and the uncoated portion and the coated portion of the negative electrode are arranged along the length of the negative electrode sheet.

[0096] It is understood that the air permeability adjustment of Examples 2, 3, 4, Comparative Examples 1, 2, and 3 can be achieved by adjusting the process parameters and stretching speed ratio during the stretching process.

[0097] Test case Separator impedance: The separator resistance Rs is measured by assembling a symmetrical cell. It can be understood that the separator resistance Rs can be obtained by assembling a symmetrical cell and testing the ionic conductivity of the coated separator. Specifically, a symmetrical cell is assembled (the symmetrical cell structure is copper foil + separator + copper foil). By changing the number of separator layers, the impedance of the cell with different numbers of separator layers is measured using EIS (electrochemical impedance spectroscopy), and a linear fit is performed. The slope is the separator impedance Rs. Then, the separator ionic conductivity is calculated using the following formula: λ = d / Rs·S, where d is the separator thickness and S is the effective area of ​​the separator.

[0098] Diaphragm puncture strength: using a universal tensile testing machine, with a specimen size of 15mm*100mm and a tensile speed of 50mm / min.

[0099] Battery DCR: At 25℃, the battery is charged at a constant current rate of 1C to the upper limit voltage of 4.2V, and then charged at a constant voltage rate to 0.05C. Then it is discharged at a 1C rate for 30 minutes (50% SOC), and then discharged at 30C for 10 seconds (sampling at 0.1s). The voltage drop ΔU and current difference ΔI are recorded. DCR = ΔU / ΔI. Data acquisition and recording: Pulse 100ms, rest for 1s, other steps 30s; Rate discharge performance test: At 25℃, the battery was charged at a constant current rate of 1C to the upper limit voltage of 4.2V, and then charged at a constant voltage rate to a current of 0.05C. Then, it was discharged at constant current rates of 1C, 3C, 5C, and 10C to the cutoff voltage of 2.7V, and the discharge capacity at each rate was recorded. The ratio of the discharge capacity at each rate to the 1C discharge capacity was calculated as the capacity retention rate, used to evaluate rate performance.

[0100] Cyclic performance test: At 25℃, charge and discharge at a rate of 10C / 10C, ​​cycle the battery from 0 to 100% SOC for 1000 cycles, and record the discharge capacity retention rate at this time.

[0101] The specific test results are shown in Table 1 below: Table 1

[0102] Results analysis: The test data shows that: 1. As the membrane permeability decreases (from 170s / 100cc to 70s / 100cc), the membrane resistance (Rs) and the battery DC internal resistance (DCR) generally show a downward trend. This indicates that lower permeability (higher porosity) is beneficial for reducing lithium-ion transport resistance.

[0103] 2. Although Comparative Example 1 (air permeability 70) has the lowest internal resistance and the highest rate retention, low air permeability usually means that the membrane pore size is too large or the pore structure is too loose. The membrane puncture reduction is significantly reduced, by 42% compared to Example 1. In actual long-term battery cycling, there may be safety hazards such as insufficient mechanical strength, increased risk of dendrite puncture, and decreased electron blocking ability.

[0104] 3. Examples 1-3 of this application (air permeability 110-150s / 100cc) achieved an excellent balance in terms of separator resistance, battery DCR, and 10C rate capacity retention. Compared to Comparative Example 2 (air permeability 170s / 100cc), the examples exhibit significantly lower internal resistance and superior rate performance. For instance, Example 3 (150s / 100cc) showed a battery DCR reduced by approximately 46% compared to Comparative Example 2 (170s / 100cc), and a 6.9% increase in 10C capacity retention.

[0105] 4. The DCR, 10C rate capacity retention, and 1000-cycle capacity retention of the Comparative Example 4 battery were significantly lower than those of the Example. When the uncoated part is arranged along the length direction, in the wound cell, the tabs need to be led out from the side of the cell, which increases the assembly difficulty and the uneven current distribution can easily cause problems such as increased internal resistance and reduced dynamic performance.

[0106] 5. Comparative Example 3 (with coating, air permeability 190s / 100cc) had the worst performance in all aspects, which verifies that although the traditional adhesive coating enhances the adhesion, it seriously deteriorates the ion transport performance.

[0107] 6. Considering both performance and safety, the membrane permeability is controlled within the range of 95-150s / 100cc (as in Examples 1-3), and the ratio between the uncoated portion and the electrode is controlled within the range of 3%~8%. This not only prevents edge short circuits and lithium plating but also maximizes energy density. Under the premise of ensuring sufficient mechanical strength and electronic insulation of the membrane, the ionic conductivity is optimized to the maximum extent, thereby achieving the best balance between low internal resistance and high rate performance of the battery.

[0108] The above embodiments are merely illustrative of the technical solutions of this application and are not intended to limit it. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and all should be covered within the scope of the specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of protection.

Claims

1. An electrode assembly, characterized in that, include: A positive electrode sheet (100) includes a positive current collector (110) and a positive active material (120). The positive current collector (110) has a positive electrode coated portion (110a) and a positive electrode uncoated portion (110b). The positive active material (120) is coated on the positive electrode coated portion (110a). The positive electrode coated portion (110a) and the positive electrode uncoated portion (110b) are arranged along the width direction of the positive electrode sheet (100). A negative electrode sheet (200) includes a negative electrode current collector (210) and a negative electrode active material (220). The negative electrode current collector (210) has a negative electrode coated portion (210a) and a negative electrode uncoated portion (210b). The negative electrode active material (220) is coated on the negative electrode coated portion (210a). The negative electrode coated portion (210a) and the negative electrode uncoated portion (210b) are arranged along the width direction of the negative electrode sheet (200). A separator (300) is disposed between the positive electrode (100) and the negative electrode (200), wherein the air permeability of the separator (300) is greater than or equal to 95s / 100cc and less than or equal to 150s / 100cc.

2. The electrode assembly according to claim 1, characterized in that, The diaphragm (300) includes at least one polyolefin layer (310).

3. The electrode assembly according to claim 2, characterized in that, The diaphragm (300) consists only of a polyolefin layer (310).

4. The electrode assembly according to claim 2, characterized in that, Along the thickness direction of the separator (300), at least one polyolefin layer (310) is located on the outermost side of the separator (300), and the polyolefin layer (310) is in direct contact with the positive electrode (100), and / or, at least one polyolefin layer (310) is located on the outermost side of the separator (300), and the polyolefin layer (310) is in direct contact with the negative electrode (200).

5. The electrode assembly according to claim 2, characterized in that, The polyolefin layer (310) includes a first fiber (311) and a second fiber (312). The first fiber (311) extends along the length direction of the diaphragm (300), and the second fiber (312) extends along the width direction of the diaphragm (300). There are multiple first fibers (311). Along the width direction of the diaphragm (300), a second fiber (312) is disposed between two adjacent first fibers (311).

6. The electrode assembly according to claim 5, characterized in that, The diameter of the first fiber (311) is larger than the diameter of the second fiber (312).

7. The electrode assembly according to claim 5, characterized in that, The diameter of the first fiber (311) is greater than or equal to 80 nm and less than or equal to 400 nm, and / or the diameter of the second fiber (312) is greater than or equal to 5 nm and less than or equal to 79 nm.

8. The electrode assembly according to claim 5, characterized in that, Along the width direction of the diaphragm (300), the size of the second fiber (312) is greater than or equal to 50 nm and less than or equal to 500 nm.

9. The electrode assembly according to claim 5, characterized in that, The polyolefin layer (310) is configured to have multiple preset regions with an area of ​​1μm*1μm, wherein the difference in diameter between any two first fibers (311) within any preset region is less than or equal to 300nm.

10. The electrode assembly according to claim 5, characterized in that, The polyolefin layer (310) is configured to have a plurality of preset regions with an area of ​​1μm*1μm, wherein the difference in diameter between any two points of any first fiber (311) within any preset region is less than or equal to 300nm.

11. The electrode assembly according to claim 5, characterized in that, The number of the second fibers (312) is multiple, and the multiple second fibers (312) are arranged at intervals along the length direction of the diaphragm (300).

12. The electrode assembly according to claim 11, characterized in that, Along the length of the diaphragm (300), the distance between two adjacent second fibers (312) is greater than or equal to the diameter of the second fiber (312).

13. The electrode assembly according to claim 5, characterized in that, The polyolefin layer (310) further includes a third fiber (313), which extends along the width direction of the diaphragm (300). Along the width direction of the diaphragm (300), the third fiber (313) is disposed between two adjacent first fibers (311). The diameter of the third fiber (313) is greater than the diameter of the second fiber (312). The diameter of the third fiber (313) is greater than or equal to 80 nm and less than or equal to 400 nm.

14. The electrode assembly according to claim 2, characterized in that, The polyolefin layer (310) has multiple layers, and the multiple polyolefin layers (310) are stacked along the thickness direction of the diaphragm (300). At least one polyolefin layer (310) is a first polyolefin layer (310a), and at least one polyolefin layer (310) is a second polyolefin layer (310b). The first polyolefin layer (310a) and the second polyolefin layer (310b) are made of different materials.

15. The electrode assembly according to claim 14, characterized in that, The diaphragm (300) includes a first polyolefin layer (310a) and a second polyolefin layer (310b) stacked together.

16. The electrode assembly according to claim 14, characterized in that, The diaphragm (300) includes a first polyolefin layer (310a), a second polyolefin layer (310b), and a first polyolefin layer (310a) stacked together.

17. The electrode assembly according to claim 2, characterized in that, The polyolefin layer (310) has multiple layers, and the multiple polyolefin layers (310) are stacked along the thickness direction of the diaphragm (300). At least one polyolefin layer (310) is a first polyolefin layer (310a), and at least one polyolefin layer (310) is a second polyolefin layer (310b). The first polyolefin layer (310a) and the second polyolefin layer (310b) have different air permeability.

18. The electrode assembly according to claim 17, characterized in that, The first polyolefin layer (310a) consists of two layers, and the second polyolefin layer (310b) consists of one layer. Along the thickness direction of the diaphragm (300), the second polyolefin layer (310b) is located between the two first polyolefin layers (310a). The air permeability of the first polyolefin layer (310a) is less than that of the second polyolefin layer (310b).

19. The electrode assembly according to claim 1, characterized in that, The electrode assembly is of the wound type.

20. The electrode assembly according to claim 1, characterized in that, The uncoated positive electrode portion (110b) extends along the length direction of the positive electrode sheet (100), and the size of the uncoated positive electrode portion (110b) is equal to the size of the coated positive electrode portion (110a). And / or, the uncoated negative electrode portion (210b) extends along the length direction of the negative electrode sheet (200), and the size of the uncoated negative electrode portion (210b) is equal to the size of the coated negative electrode portion (210a).

21. The electrode assembly according to claim 1, characterized in that, Along the width direction of the positive electrode (100), the ratio of the size of the uncoated portion (110b) to the size of the positive electrode (100) is greater than or equal to 3% and less than or equal to 8%, and / or, along the width direction of the negative electrode (200), the ratio of the size of the uncoated portion (210b) to the size of the negative electrode (200) is greater than or equal to 3% and less than or equal to 8%.

22. The electrode assembly according to claim 1, characterized in that, Along the length of the electrode assembly, the uncoated positive electrode portion (110b) and the uncoated negative electrode portion (210b) are located at opposite ends of the electrode assembly.

23. The electrode assembly according to claim 1, characterized in that, The thickness of the diaphragm (300) is greater than or equal to 6 μm and less than or equal to 20 μm.

24. The electrode assembly according to claim 1, characterized in that, The electrode assembly includes at least one of the following: Along the length of the electrode assembly, the size of the electrode assembly is greater than or equal to 120 mm and less than or equal to 150 mm; Along the width direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 60 mm and less than or equal to 80 mm; Along the thickness direction of the electrode assembly, the size of the electrode assembly is greater than or equal to 12 mm and less than or equal to 20 mm.

25. The electrode assembly according to claim 1, characterized in that, The diaphragm (300) is made of at least one of polyethylene and polypropylene.

26. The electrode assembly according to any one of claims 1 to 25, characterized in that, The positive electrode active material (120) includes at least one of secondary spherical particles, single crystal particles, and single crystal-like particles.

27. The electrode assembly according to claim 26, characterized in that, The positive electrode active material (120) includes secondary spherical particles and has a porous structure.

28. The electrode assembly according to any one of claims 1 to 25, characterized in that, The positive electrode active material (120) includes a layered lithium transition metal oxide; the transition metal in the layered lithium transition metal oxide includes nickel and manganese; and the molar percentage of nickel in the transition metal is 30% to 55%, and the molar percentage of manganese in the transition metal is 25% to 35%.

29. The electrode assembly according to any one of claims 1 to 25, characterized in that, The positive electrode active material (120) includes lithium iron phosphate.

30. A single battery cell, characterized in that, Includes the electrode assembly as described in any one of claims 1 to 29.

31. A battery pack, characterized in that, Includes the battery cell as described in claim 30.

32. An electrical appliance, characterized in that, Includes the battery pack as described in claim 31.